Metabolic characteristics and muscle damage profile of repeated bouts of eccentric cycling in comparison to concentric cycling - Penailillo, L.; Blazevich, A.; Numazawa, H.; Nosaka, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Metabolic cost of eccentric (ECC) cycling is lower at a given intensity (1), and ECC cycling training produces greater muscle mass and strength gains compared with concentric (CON) cycling (2). ECC cycling has been reported to result in prolonged strength loss and myofibrillar disruption (3). It is important to know muscle damage profile in ECC cycling to safely implement it in training. Although it is well known that the magnitude of muscle damage is attenuated when the same ECC exercise is repeated, it is unknown whether this is also the case for ECC cycling. Thus, this study compared the first and second ECC cycling bouts and a bout of CON cycling. Methods: Ten men (28.4 ± 8.2 y) performed a single bout of CON cycling and two bouts of ECC cycling with a two-week interval between bouts. All bouts consisted of 30 min cycling at 60% of the maximal CON power output at 60 rpm (169.2 ± 52.6 W). Heart rate (HR), oxygen consumption (VO2), blood lactate (BLa) and rate of perceived exertion (RPE) were measured during cycling, and tympanic temperature (TEMP) was assessed before and immediately after cycling. Maximal voluntary isometric contraction strength of knee extensors (MVC), squat jump (SJ) and counter movement jump height (CMJ), muscle soreness and plasma creatine kinase activity (CK) were measured before, immediately after and 1-4 days after exercise. Changes in these variables over time were compared across the three bouts by a two-way repeated measures ANOVA. Results: The average HR, VO2, BLa and RPE were lower (P<0.05) during the first ECC cycling (ECC1) than CON cycling, and HR and BLa were even lower (P<0.05) during the second ECC cycling (ECC2) compared with ECC1. TEMP increased only after CON cycling by 0.45°C. Decreases in MVC, CMJ and SJ, and increase in muscle soreness were greater (P<0.05) after ECC1 than CON and ECC2. Increases in CK were small after all bouts. Following ECC2, little changes in the variables were found such that MVC, CMJ and SJ did not decrease from baseline and no muscle soreness was developed, which were similar to those seen after CON. Discussion: The results confirmed that ECC cycling is less metabolically demanding than CON cycling at the same work. The new findings of the present study were that metabolic demand was further reduced during the second than the first ECC cycling bout, and muscle damage was little or minimum after the second ECC cycling. This is in line with the repeated bout effect shown in other ECC exercises. Thus, muscle damage should not limit the use of ECC cycling.